(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
This study evaluated the timeliness cost, and muscle energy needs of a nylon string-blade mower, commonly used for small lawn maintenance. It utilized a penalty-based model to quantify the decline in lawn aesthetics, by expressing it as a monetary penalty when mowing is delayed. Aesthetic loss in terms of reduction in lawn appeal caused by excessive grass height, clumping of cuttings, or thatch accumulation were considered in this study, and found to reduce acceptability of the lawn for its intended use. Heart rate, a physiological workload index, was used to estimate muscle energy expenditure based on ergometer calibration, while rate of perceived exertion was used to assess the physiological strain. Results from the study show that the optimal mowing interval was found to be 14 days, with hourly losses of N114.52/ha for early mowing and N890.48/ha for delayed mowing. When accounting for lawn aesthetics losses, the total average mowing cost increased by an hourly amount of N114.52 per hectare for early mowing and N678.55 per hectare for delayed mowing. 40.96 W muscle work rate, corresponding to operator heart rate of 127 bpm was observed for the mowing, and was perceived as a light intensity task. The equivalent sound pressure level recorded at the operator’s ears distance to the exhaust outlet was found to be 62.5 dB during mowing. These were within the recommended safety limits, ensuring that operators are not exposed to excessive work rate or hazardous noise levels. These findings will offer lawn managers minimized cost and safer mowing decisions support.